1992
DOI: 10.1002/jso.2930490104
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunological evaluation of intraoperative radiation therapy for patients with unresectable pancreatic cancer

Abstract: The clinical efficacy of intraoperative radiation therapy (IORT) and the changes of immunological parameters were investigated. Nine patients with unresectable pancreatic cancer were treated with IORT (2,500-3,500 cGy) and the changes of various immunological parameters were compared with those in 11 patients with advanced cancer who received external beam irradiation therapy (XRT), 2,500-3,500 cGy. After IORT, 71% of patients obtained pain relief, two of the nine patients showed a partial response, and the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…5 Indeed, our patient had a duodenal outlet obstruction, and thus had to undergo a bypass operation. We previously reported that IORT has immunoregulatory effects which do not inhibit antitumor immunity, 6 and IORT may thus translate into an extended survival in our patient.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…5 Indeed, our patient had a duodenal outlet obstruction, and thus had to undergo a bypass operation. We previously reported that IORT has immunoregulatory effects which do not inhibit antitumor immunity, 6 and IORT may thus translate into an extended survival in our patient.…”
Section: Discussionmentioning
confidence: 90%
“…5 In IORT a high single radiation dose should be delivered to a surgically defined area, while carefully protecting all uninvolved organs and tissue. 6 The present case report is the first to describe the therapeutic effects of IORT for bulky non-Hodgkin's lymphoma developing in a patient after undergoing extensive multiagent chemotherapy.…”
Section: Introductionmentioning
confidence: 95%
“…Multiple studies focusing on patients with cancer undergoing radiotherapy also unveiled reductions in the absolute number of various peripheral blood (PB) lymphocyte subsets, including NK cells [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ], and impaired NK cell activity compared to pre-treatment levels [ 26 , 27 ], suggesting that radiotherapy directly decreases both NK cell viability and function in a dose-dependent manner.…”
Section: Radiotherapymentioning
confidence: 99%
“…Unfortunately, IORT may also inhibit the activity of tumour infiltrating lymphocytes. The restriction of this natural killer activity means that IORT is best provided with biological response modifiers to counter such inhibition of local immunity 165 if the theoretical advantages provided by IORT are to be fully translated into survival benefit for patients.…”
Section: The Role Of Radiotherapy or Chemoradiotherapymentioning
confidence: 99%